Surprising widespread Cymodocea nodosa occurrence along Israel’s Mediterranean coast and Implications for Seagrass Conservation in a hotspot of climate change - HEPNER UCKΟ, ORI; ARLÉ, EDUARDO; MALAMUD, SHAHAR; WINTERS, GIDON; BELMAKER, JONATHAN (Mediterranean Marine Science, 2024)
Cymodocea nodosa is a temperate seagrass that grows in shallow and sheltered waters of the Mediterranean Sea. Although it is found in both the western and eastern basins, it was thought to be absent from the extremely warm and salty waters along the Israeli coastline, the most eastern part of the Mediterranean. We conducted methodical, seasonal, towed-diver surveys along the Mediterranean coast of Israel, recording position, depth, presence/absence of C. nodosa, seabed characteristics, and habitat complexity. We used general additive models (GAMs) to understand how the combination of depth, latitude (space), and season (time), explained the distribution of local meadows. We then compared the habitat affinity of these Israeli meadows with other sites in the Eastern Mediterranean by conducting a systematic literature review and using Species Distribution Models (SDMs). Underwater surveys unveiled the extensive distribution of C. nodosa over a narrow depth range of 8-21m (with peak occurrence at 14m) in exposed habitats. These locations are distinct from other Eastern Mediterranean populations, in which C. nodosa is found in shallower and sheltered habitats. SDMs confirmed the increase in the geographical range also reflects an increase in realized niche breadth into higher values of temperatures, salinity, and current velocity. Considering that the eastern tip of the Mediterranean is a climate change hotspot, finding C. nodosa populations surviving these harsh conditions holds implications for seagrass conservation and restoration in the entire Mediterranean. However, the low density of observed meadows suggests that these populations require careful monitoring to prevent local extirpation.